Determinant Factors of Infrastructure Firm’s Value in Indonesia Stock Exchange - Jasen Sugiarto Effendy; Ignatius Roni Setyawan (International Journal of Application on Economics and Business, 2023)
This study will test whether profitability, solvency and firm size have influenced to the firm value for the infrastructure sector companies listed in IDX. Using the purposive sampling, this study obtains 30 companies from the 2018-2021 so that the total number of observations is 120 firm-years. The analysis result conducted by data panel regression shows that profitability and firm size have a significant effect on the firm value at level 10% and 5% respectively. The other finding is that solvency does not affect firm value. From this result, the study will imply that infrastructure sector firms in IDX have considered profitability and size in the effort of maximizing the company value and they actually tend not to use debt as the major regular financing sources.